Genome-wide association study of motor coordination problems in ADHD identifies genes for brain and muscle function - Fliers, Ellen A.; Banaschewski, Tobias (The world journal of biological psychiatry, 2012)
Objectives. Motor coordination problems are frequent in children with attention deficit/hyperactivity disorder (ADHD). We performed a genome-wide association study to identify genes contributing to motor coordination problems, hypothesizing that the presence of such problems in children with ADHD may identify a sample of reduced genetic heterogeneity. Methods. Children with ADHD from the International Multicentre ADHD Genetic (IMAGE) study were evaluated with the Parental Account of Children's Symptoms. Genetic association testing was performed in PLINK on 890 probands with genome-wide genotyping data. Bioinformatics enrichment-analysis was performed on highly ranked findings. Further characterization of the findings was conducted in 313 Dutch IMAGE children using the Developmental Coordination Disorder Questionnaire (DCD-Q). Results. Although none of the findings reached genome-wide significance, bioinformatics analysis of the top-ranked findings revealed enrichment of genes for motor neuropathy and amyotrophic lateral sclerosis. Genes involved in neurite outgrowth and muscle function were also enriched. Among the highest ranked genes were MAP2K5, involved in restless legs syndrome, and CHD6, causing motor coordination problems in mice. Further characterization of these findings using DCD-Q subscales found nominal association for 15 SNPs. Conclusions. Our findings provide clues about the aetiology of motor coordination problems, but replication studies in independent samples are necessary.
Published online: 07 Apr 2011
Gesehen am 05.04.2018